Assessing the Feasibility of Drone‐Mediated Vaccine Delivery: An Exploratory Study - Sumit Aggarwal; Prakamya Gupta; Sivaraman Balaji; Saurabh Sharma; Ajoy Kanti Ghosh; Simmy; Balram Bhargava; Samiran Panda (Health Science Reports)
ABSTRACT Background and Aims In the past decade, unmanned aerial systems (UASs), commonly known as drones, have found applications not only in military and agriculture but also in the transportation of medical supplies. Purpose The present study was conducted to assess the practicality of utilizing drones as a mode for the delivery of vaccines to combat the challenges. Study Design An exploratory study. Methodology Due to the COVID‐19 pandemic restrictions and paucity of availability of rules and regulations related to drones in India in 2021, this study was conducted as a exploratory study for which number of regulatory approvals are obtained and it involves five drone missions within the premises of the Indian Institute of Technology (IIT), Kanpur, India on a confined airstrip of 3 km2 to transport simulated vaccine vials using a multi‐rotor top‐load UAS in the normal weather conditions in daylight where dummy vaccine vials (COVID‐19) were packed with cool packs to maintain the temperature. Study was conducted to explore feasibility to carry vaccines through drones and any environmental impact on the vaccine vials while its transportation. Results The drones demonstrated a maximum flight endurance of 31 min while carrying a payload of up to 4.5 Kg, covering an aerial distance of 17 km at an average speed ranging at 12 m per second. Notably, the vaccine carrier box was able to maintain a recommended temperature of 3°C–4°C throughout the transportation process, and there is no impact of vibration on the physical integrity and leakage of the vaccine vials during flight. Conclusions These findings signify the potential for the drone‐based medical supply deliveries across confined and controlled environment conditions. This study provides the insights that there is no environmental impact such as humidity, temperature, wind etc on the drone and no impact on vibrations on the physical integrity and leakage of the dummy vaccine vials. There were few regulatory barriers that required special approvals from concerned authorities. The study was not designed to assess for cost‐effectiveness, also it was conducted in defined geography so all sorties were VLOS. Study has various limitations such as using simulated vaccine vials, regulatory barriers, operational barriers etc. Conducting the study in a controlled environment at IIT Kanpur limits generalizability. In spite of these limitations this study provides valuable insights and may explore a diverse environment that can help in strengthening health services especially in difficult terrains.